USING THE THINK PAIR SHARE LEARNING MODEL WITH IMAGE MEDIA TO IMPROVE NEGOTIATION TEXT WRITING SKILLS IN STUDENTS OF CLASS X IPA SMA AL MULTAZAM SEPATAN ACADEMIC YEAR 2022/2023 - Sueni, Ucun; Goziyah, Goziyah; Marzuki, Ismail (Jurnal Dinamika UMT, 2023)
Based on the results of data analysis, hypothesis testing, and discussion that has been carried out, it can be revealed that: The use of an Integrative Approach in the listening and writing skills of class VIII MTs Nurul Falah Kutabumi is able to improve student learning outcomes, the Integrative Approach is felt to be more effective than using other approaches with the effectiveness weight is 21.7%, and the results of the ability to listen and write news for class VIII students increase more after using the Integrative Approach. This is indicated by the average value of the experimental class 78.40 which is greater than the average value of the control class 67.28.